Pemanfaatan Google Sites sebagai Media Pembelajaran Digital Interaktif dalam Pembelajaran Matematika: Studi Kasus di Sekolah Menengah Atas : Utilizing Google Sites as an Interactive Digital Learning Media in Mathematics Learning: A Case Study in High School - Jelita Fuji Khaebibah; Surya Amami Pramuditya (Jurnal Pendidikan Sains dan Komputer, 2026)
The development of digital technology is driving the transformation of learning toward the use of interactive, flexible, and student-centred learning media, particularly in mathematics instruction in Senior High Schools (SMA). Challenges that are still frequently encountered include limited face-to-face time, limited variety of learning media, and the need for readily accessible independent learning resources. This study aims to analyse the accessibility of Google Sites-based mathematics learning media and to evaluate user feedback and experience with these media, developed as a digital learning hub. The study used a descriptive-evaluative approach with a single-case design. The research subjects included three peers serving as expert assessors, one mathematics teacher, and three high school students as actual users. The research instrument was a Likert-scale questionnaire covering technical, pedagogical, aesthetic, and interactivity aspects, supplemented by open-ended comments. Data were analysed descriptively and thematically. The results showed that the media received an average peer-assessment score of 4.25, categorised as "Very Good," particularly in the technical and learning feasibility aspects. User feedback indicated an average score of 4.76 from teachers, and 4.50 from students, both categorised as "Very Good." The media was deemed accessible, visually engaging, and helpful in understanding mathematical concepts. However, the evaluation indicated a need for improvement in conceptual interactivity, instructional clarity, and the provision of formative feedback. Overall, Google Sites was deemed effective as an interactive digital learning tool that supports independent mathematics learning at the high school level.